Penguatan Pendidikan Karakter di SD Negeri 104197 Klambir - Rahman, Fadya Safitri; Widia, Friska; Zainuri, Humairo Sakinah; Sari, Putri Puspita; Hasibuan, Safran (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to describe the Strengthening of Religious Character Education (PPK), nationalism, independence, mutual cooperation and integrity in elementary school SD NEGERI 104197 KLAMBIR. The research approach used is a qualitative approach. The research subjects were school principals and teachers. Data collection techniques use interviews and observation. The results of this research conclude: strengthening religious character education is integrated into classroom learning and religious activities. Strengthening nationalist character education through routine flag ceremonies every Monday, and extra-curricular activities for paskibra. Strengthening independent character education, namely that students are required to take part in scout extracurricular activities. Strengthening mutual cooperation character education, namely students cleaning the environment together and completing tasks through study groups. Strengthening integrity character education, namely students are responsible for the picket schedule given.